Comparison of the Therapeutic Effectiveness of Triple Versus Quadruple Therapy for Helicobacter pylori - Loghmari, Mohamed Hichem; Aissaoui, Firas; Guediche, Arwa; Bouhlel, Wided; Zakhama, Mejda; Chaabene, Nabil B.; Rehaiem, Amel; Abdeljalil, Nouha Ben; Njima, Manel; Zakhama, Abdelfetteh; Kadri, Yosr; Mastouri, Maha; et al. (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Background: Traditional treatment for Helicobacter pylori (H. pylori) includes proton pump inhibitors and triple therapy, and this treatment has become unsuitable for eliminating H. pylori. Most learned societies recommend concomitant quadruple therapy (QC) as a first-line alternative therapy for this bacterial infection. Currently, there is a notable absence of studies in Tunisia that directly compare the efficacy and outcomes of triple therapy versus quadruple therapy. Aim: The aim of this study is to compare the efficacy and safety of triple therapy (TT) with QC for the eradication of H. pylori infection. Methods: A parallel double-blind randomized controlled trial was conducted. The diagnosis of H. pylori infection was made by pathological examination of gastric biopsies. Patients were randomly assigned to two treatment groups: either QC (esomeprazole 80 mg, amoxicillin 2000 mg, clarithromycin 1000 mg, and metronidazole 1000 mg daily) or triple therapy (esomeprazole 80 mg, amoxicillin 2000 mg, and clarithromycin 1000 mg daily in divided doses) for 14 days. The efficacy of the treatment is defined by H. pylori eradication attested by a negative breath test performed 6 weeks after the completion of treatment. The significance level was set at p < 0.05 for all statistical tests. Variables significant at 20% in univariate analysis were introduced into binary logistic regression for a multivariate analysis. Results: Ninety-two patients were included. Forty-two patients belonged to the QC group and 50 to the TT group. No significant difference was noted between the two groups concerning the rate of H. pylori eradication either by intention to treat (81% vs. 72% respectively, p = 0.31) or per-protocol (81.6% vs. 76.1% respectively, p = 0.54). Likewise, there was no difference between the two groups in terms of tolerance to treatment (59.5% for QC vs. 58% for TT, p = 0.88). No factor has been associated with treatment failure. Eradication regimens should be based on the best locally effective regimen, ideally using individual susceptibility testing, or antibiotic consumption data and clinical outcome data. Conclusion: There was no significant difference in the rate of HP eradication between the QC and the 14-day triple therapy.